PENGARUH USER INTERFACE (UI) DAN USER EXPERIENCE (UX) TERHADAP MINAT BELI ULANG AKUN NETFLIX - Adithia Anggrahi Marjani Asniati; Finnah Fourqoniah (Bajang Institute, 2023)
Nowadays, there are more types of entertainment for the global community, one of which is the type of entertainment service or commonly referred to recently as a application Video-On-Demand, for example, Indonesian people recognized and used this entertainment service, along with the increase in internet users and because of that even distribution of the internet network in Indonesia. One of the (VOD) that has been widely recognized and used by the Indonesian people is Netflix. Netflix is one of the many digital platforms that are recognized and used by the global community, especially Indonesians, people use Netflix as a means to watch series, movies, or shows that Netflix presents. When users feel happy and satisfied when and after using Netflix, of course, users tend to continue to subscribe or repurchase their Netflix account to still be able to use Netflix. In the use of the application (VOD) Netflix, of course, it cannot be separated from the user interface and user experience. The purpose of this study was to find out whether the user interface and user experience had a positive impact on repeat buy interest or subscription interest for Netflix accounts. Data for this study was obtained from questionnaires disseminated through Google Forms. This study used a descriptive procedure for quantification with a survey approach and the data were processed in SPSS version 25. Based on the results of research and data processing carried out, it is determined that the user interface does not have a significant effect on repurchase interest in the Netflix account, while user experience partially affects buying interest. Reset your account or subscribe to Netflix. The user interface and user experience have a huge impact on account repurchases and interest in Netflix subscriptions